Education and Introduction of Cucumbar Juice as a Natural Alternative for Reducing Blood Pressure among Hypertensive Patients in Ciomas District - Rizqa Wahdini; Khalida Sibualamu; Ratu Chairunisa (CV. Paperhome Indonesia, 2025)
Hypertension is one of the leading non-communicable diseases contributing to high morbidity and mortality rates in Indonesia. Natural management of hypertension through lifestyle modifications and the consumption of healthy foods is increasingly favored as a complementary therapy. Cucumber juice is known to contain active compounds with the potential to lower blood pressure. This community service program aimed to provide education and introduce cucumber juice as a natural alternative for reducing blood pressure among individuals with hypertension in Ciomas, Bogor. A total of 40 hypertensive participants took part in activities that included educational sessions, demonstrations on how to prepare cucumber juice, and blood pressure measurements before and after the intervention. The results showed an average decrease of 14.8 mmHg in systolic blood pressure and 8.4 mmHg in diastolic blood pressure after consuming cucumber juice for seven consecutive days. Additionally, participants' knowledge regarding hypertension and the benefits of cucumber juice significantly improved, as evidenced by pre-test and post-test assessments. This activity demonstrates that cucumber juice can serve as an effective natural alternative to help lower blood pressure, and highlights the importance of education in raising public awareness about hypertension management. Further research with a larger sample size and extended duration is recommended to validate these findings.